Micrografting technique for cloning Hashab [Acacia senegal (L.) Willd]: Effect of rootstock age, scion length, scion source, sucrose and light duration - Altayeb, Ghada; Ali, Mohamed (Gezira Journal of Agricultural Science; Vol 11 No 2 (2013), 2013)
Hashab [ Acacia senegal ( L.) Willd] is considered as an important tree species in Sudan which produces gum Arabic. It is mainly propagated by seeds, which result in variation in yield due to segregation. This study was established to develop an in vitro micrografting technique for cloning Hashab trees. Five experiments were conducted during 2012 to investigate the effects of age of rootstock seedling, scion length, scion source, sucrose, and light duration on the success of micrografting of Hashab in a completely randomized design with ten replicates. Two and four weeks- old seedlings were tested as rootstocks. They were grafted with scions obtained from the greenhouse. The two weeks-old seedlings had significantly higher percentage of successful grafts, and scion morphogenesis. Different scion lengths (1-1.5 cm and 2.5-3cm) were tested.  Scions 1-1.5cm long had significantly higher rates of successful micrografts. Scions obtained from different sources (greenhouse, in vitro plantlet, and mature tree) were evaluated and those obtained from the greenhouse gave significantly higher percentages of successful grafts, number of leaves, number of nodes, and an increase in shoot length. Different concentrations of sucrose (20, 30, 40, 50, and 60 g/l) were tested and grafted plants at 40g/l sucrose gave significantly higher percentages of successful grafts. Incubation of micrografted seedlings under continuous light for two weeks gave significantly higher percentages of successful grafts.      تعتبر شجرة الهشاب من الأنواع الشجرية المهمة في السودان لإنتاج الصمغ العربي. يتم عادة إكثار الهشاب عن طريق البذور مما ينتج عنه اختلاف في الإنتاجية نتيجة للتلقيح الخلطي. تهدف هذه الدراسة لتطوير تقنية التطعيم الدقيق لشجرة الهشاب. نفذت خمس تجارب لاختبار أثر عمر أصل شتلات الهشاب و طول الطعم و مصدر الطعم و تركيز السكر في الوسط الغذائي وفترة الإضاءة في إنجاح التطعيم الدقيق في تصميم كامل العشوائية بعشرة مكررات. أظهرت النتائج أن الأصل الذي عمره أسبوعين من شتلات الهشاب أعطى أعلى نسبة نجاح للطعم الدقيق للهشاب. وجد أن الطعم الذي طوله 1.5 -1 سم أعطى أعلى نسبة نجاح معنوي للطعم الدقيق للهشاب. النباتات النامية في البيوت المحمية هي أفضل مصدر للطعم حيث أعطت أعلى نسبة نجاح للطعم الدقيق و عدد الأوراق و عدد العقد و زيادة ارتفاع السوق الخضرية للهشاب. زادت نسبة نجاح الطعم الدقيق بتركيز السكر 40 جراما للتر في الوسط الغذائي. يمكن الحصول على نسبة نجاح أعلى للطعم الدقيق عند وضع النبيتات في حضانة تحت ظروف الإضاءة المستمرة لمدة أسبوعين.